Study on Contact Force and Vibration Characteristics of Composite Cylindrical Roller Bearing. (7th October 2022) - Qu, Tie; Bian, Qiang; Zeng, Guang; Zhao, Chunjiang; Zhang, Xiangyun; Ma, Lifeng; Chen, Ming
Abstract : The composite cylindrical roller is composed of a hollow cylindrical roller and a filler body and is a new type of structure roller bearing. In order to explore the influence of different parameters on the contact characteristics and vibration characteristics of bearings, finite element models of static contact, modal analysis, and harmonic response analysis of composite cylindrical roller bearings were established based on ABAQUS software. The effects of filling rate, radial force, and the number of rollers on parameters such as contact force, contact stress, and natural frequency were studied. The results show that when the filling rate of the cylindrical roller increases from 0% to 70%, the natural frequency of bearing and the peak frequency of its harmonic response decrease, the force distribution in the contact area is also more uniform, and the maximum contact stress of the roller is reduced by 29.1%; the radial force has no effect on the peak frequency of the harmonic response of the bearing, but the increase of the radial force will increase the peak value of the response displacement, and the contact force and stress of the rollers will also increase. When the number of rollers increases from 11 to 15, the natural frequency and the peak frequency of harmonic response increase, the peak displacement decreases, the contact force distribution of the rollers in the bearing area is more uniform, and the maximum contact stress of the roller is reduced by 21.1%. The research result can provide a theoretical reference for the structural optimization and engineering application of elastic composite cylindrical roller bearings.